Coracoid Process—A Hub of Shoulder Ligaments - Desai, Sanjay; Patil, Nandakishore G.; Kapoor, Tushar (Indian Journal of Radiology and Imaging, 2022)
Coracoid process is a hook-like structure connected with multiple ligaments. The complexity and its close relations often create confusion. The aim of this study is to identify the ligaments attached to the coracoid process as discrete structures on 3T magnetic resonance imaging (MRI) scans. This is a retrospective observational study. One-hundred twenty MRI shoulder studies performed during November and December 2019 at Dept of Radiology, Deenanath Mangeshkar Hospital, Pune, were evaluated. These were obtained on 3T MRI (Siemens, Pennsylvania, United States) machine. All scans were evaluated by two experienced musculoskeletal radiologists. The ligaments studied were coracohumeral (CHL), coracoclavicular (CCL), coracoacromial (CAL), and coracoglenoid (CGL) ligaments. Mean age of cohort was 56.3 years with 59.2% males and 56.2% right shoulder studies. Pain was the main presenting symptom (49%) followed by instability (35%). Reader 1 identified CHL in 106 out of 120 and reader 2 identified 108 out of 120 on all 3 planes. Substantial interobserver agreement (κ =0.65) was noted for sagittal T1 and proton density fat saturated (PDFS) sequences. Both readers could identify CCL and CAL ligaments in all three sequences with better confidence on nonfat saturated sagittal images. Reader 1 identified CGL in 9 on axial and 12 on sagittal images among 120 cases. Reader 2 identified CGL in 13 on axial and 16 on sagittal images among 120 cases. With a κ = 0.702 for the axial PDFS and κ = 0.72 for sagittal T1 and PDFS sequence, substantial interobserver agreement was noted. Sagittal images were better in the evaluation of CGL. Identifying ligaments attached to coracoid on MRI helps in managing associated pathological states.
Keywords: capsuloligamentous complex; coracoglenoid ligament; coracohumeral ligament; coracoclavicular ligament; coracoacromial ligament